2018
DOI: 10.1016/j.toxrep.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological safety evaluation of freeze-dried Protaetia brevitarsis larva powder

Abstract: HighlightsGeneral toxicity and genotoxicity of freeze-dried P. brevitarsis larva powder was investigated.In rats, LD50 and NOAEL set at >5000 and 3000 mg/kg, respectively.No aberrant changes in Ig E and histamine concentration were observed in the 13-week oral repeated dose study.No evidence of mutagenic and carcinogenic potential was observed in the genotoxicity studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Noh et al. () also reported no toxicological observations with Orotaetia brevitarsis powder (5 g/kg body weight) from the growth curve and gross pathological findings in female rats. Therefore, locust powder is not expected to be toxic as a food material when acutely administered at a dose of 20 g/kg body weight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Noh et al. () also reported no toxicological observations with Orotaetia brevitarsis powder (5 g/kg body weight) from the growth curve and gross pathological findings in female rats. Therefore, locust powder is not expected to be toxic as a food material when acutely administered at a dose of 20 g/kg body weight.…”
Section: Resultsmentioning
confidence: 99%
“…From the results of biochemical parameters in plasma, no significant differences were observed in both sub‐chronic toxicological experiments. No aggravations in the plasma biochemical parameters of rats were reported from the chronic feeding investigations using some edible insects ( Tenebrio molitor , Pachymerus nucleorum , and Protaetia brevitarsis ; Alves et al., ; Han et al., ; Noh et al., ) From the results of hematological parameters, the values of RBC, hemoglobin, and hematocrit were significantly lower in rats fed locust powder containing diets (1% and 3%), but the differences were limited in the 28‐day sub‐chronic toxicological experiments. These differences are considered to be a transient event as the plasma levels of iron and other parameters were not significantly changed in both experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, toxicity and quality control issues associated with alternative medicines for public consumption are areas of increasing concern due to the lack of scientific documentation regarding their toxicity (Shin, Lee, Kim, et al., 2012 ). In a 13‐week oral repeated dose toxicity study, (Noh et al., 2018 ) reported that PBE shows no toxicity up to 3,000 mg/kg. In this study, we did not observe any significant changes in bodyweight and hepatic enzyme activities among experimental groups during the experimental period.…”
Section: Discussionmentioning
confidence: 99%
“…PBS is a species of the family Coleoptera found in East Asia and Europe (Noh et al . 2018). PBS at different growth stages have been reported to possess high antioxidant effects, and antimicrobial peptides protaetins can also be purified from PBS larvae (Yoon et al .…”
Section: Introductionmentioning
confidence: 99%